Sex differences in the left and right hemifields of normal subjects with computerised static perimetry. - Cohn, H (1994)
Results of routine perimetric testing of the left and right hemifields in normal subjects have been assumed to be symmetric although asymmetry due to hemispheric dominance has been established for other psychophysical tests. These asymmetries have sometimes been related to sex. With the advent of computerised static perimetry, subtle differences between the left and the right hemifields might be found that were not obvious before. This study investigated differences in retinal sensitivity between the hemifields and the role of sex and eye dominance. Forty three unequivocally right handed and right eye dominant normal adult volunteers, 24 females and 19 males, underwent Humphrey 24-2 testing, half beginning with the left eye, the other half with the right eye. The Peridata program was used to calculate decibel totals per hemifield. Four subjects were excluded because of poor cooperation or test artefacts. In females, the total of the left hemifield was significantly less than the right (p < 0.01) by a mean 18.2 (SD 24) dB equivalent to a difference of 0.34 dB per tested point. No significant difference in hemifields was found for males, between the sexes for both eyes combined, or between the two eyes for either sex. It was concluded that asymmetries in retinal sensitivity with respect to the vertical axis may be physiological and found in females, but not in males.